Ultra early cranial and spinal metastasis in a post-operative case of 4th ventricle medulloblastoma case: a case report - Kumar, Abhishek; Gupta, Sajag; Tiwari, Saurabh Kumar (International Surgery Journal, 2025)
Medulloblastoma is a type of brain tumour that occurs primarily in children and is relatively rare in adults. It has a tendency to spread through the cerebrospinal fluid pathways and can metastasize to other parts of the body, including the bones. Osseous extra-neural metastasis is uncommon, but the radiologic findings are usually sclerotic, lytic, or mixed when it occurs. In this paper, we present a case of medulloblastoma metastasizing to the cervical, dorsal and lumbar spine as well as intracranial spread and describe the magnetic resonance appearance of the lesion and also emphasize the importance of recognizing the imaging findings of metastatic lesions in patients with a history of medulloblastoma.